INFORMATICS IN GAMES FOR ELEMENTARY SCHOOL - Seidametova С.М.; Medzhitova Л.М.; Shcarban Ф.В. (Journal of Information Technologies in Education (ITE), 2012)
We discuss about the problem of using of special games software in education in order to improve and to develop cognitive activity of elementary school’s students. We present the methodical approach of teaching informatique in the elementary school.